An Ethyl Acetate Extract of Eryngium carlinae Inflorescences Attenuates Oxidative Stress and Inflammation in the Liver of Streptozotocin-Induced Diabetic Rats - Cristian M. Trejo-Hurtado; Cinthia I. Landa-Moreno; Jenaro Lemus-de la Cruz; Donovan J. Peña-Montes; Rocío Montoya-Pérez; Rafael Salgado-Garciglia; Salvador Manzo-Avalos; Christian Cortés-Rojo; Juan Luis Monribot-Villanueva; José Antonio Guerrero-Analco; Alfredo Saavedra-Molina (MDPI AG, 2023)
Secondary metabolites such as flavonoids are promising in the treatment of non-alcoholic fatty liver disease (NAFLD), which is one of the complications of diabetes due to oxidative stress and inflammation. Some plants, such as Eryngium carlinae, have been investigated regarding their medicinal properties in in vitro and in vivo assays, showing favorable results for the treatment of various diseases such as diabetes and obesity. The present study examined the antioxidant and anti-inflammatory effects of the phenolic compounds present in an ethyl acetate extract of the inflorescences of Eryngium carlinae on liver homogenates and mitochondria from streptozotocin (STZ)-induced diabetic rats. Phenolic compounds were identified and quantified by UHPLC-MS. In vitro assays were carried out to discover the antioxidant potential of the extract. Male Wistar rats were administered with a single intraperitoneal injection of STZ (45 mg/kg) and were given the ethyl acetate extract at a level of 30 mg/kg for 60 days. Phytochemical assays showed that the major constituents of the extract were flavonoids; in addition, the in vitro antioxidant activity was dose dependent with IC50 = 57.97 mg/mL and IC50 = 30.90 mg/mL in the DPPH and FRAP assays, respectively. Moreover, the oral administration of the ethyl acetate extract improved the effects of NAFLD, decreasing serum and liver triacylglycerides (TG) levels and oxidative stress markers and increasing the activity of the antioxidant enzymes. Likewise, it attenuated liver damage by decreasing the expression of NF-κB and iNOS, which lead to inflammation and liver damage. We hypothesize that solvent polarity and consequently chemical composition of the ethyl acetate extract of E. carlinae, exert the beneficial effects due to phenolic compounds. These results suggest that the phenolic compounds of the ethyl acetate extract of E. carlinae have antioxidant, anti-inflammatory, hypolipidemic, and hepatoprotective activity.